Folic Acid and Risk of Preterm Birth: A Meta-Analysis - Li, Bingbing; Zhang, Xiaoli; Peng, Xirui; Zhang, Shan; Wang, Xiaoyang; Zhu, Changlian (Frontiers in Neuroscience, 2019)
The results from epidemiologic studies linking blood folate concentrations, folic acid supplementation, or dietary folate to the risk of preterm birth are inconsistent. In this study, we aimed to summarize the available evidence on these associations. A systematic search of the PubMed/MEDLINE, Google Scholar, Web of Science, and Cochrane Library databases up to October 20, 2018 was performed and reference lists of retrieved articles were screened. Pooled odds ratios (ORs) and 95% confidence intervals (CIs) for the highest vs. the lowest levels of folate concentrations, folic acid supplementation, and dietary folate were calculated using random-effects models. Subgroup analyses and univariate meta-regression were performed to explore the sources of heterogeneity. Ten studies (six prospective cohort studies and four case-control studies) were included on folate concentrations, 13 cohort studies were included about folic acid supplementation, and 4 cohort studies were included regarding dietary folate intake. Higher maternal folate levels were associated with a 28% reduction in the risk of preterm birth (OR 0.72, 95% CI 0.56–0.93). Higher folic acid supplementation was associated with 10% lower risk of preterm birth (OR 0.90, 95% CI 0.85–0.95). In addition, a significant negative association was observed between dietary folate intake and the risk of preterm birth (OR 0.68, 95% CI 0.55–0.84), but no significant relation was seen between dietary folate and the risk of spontaneous preterm birth (OR 0.89, 95% CI 0.57–1.41). In the subgroup analysis, higher maternal folate levels in the third trimester were associated with a lower risk of preterm birth (OR 0.58, 95% CI 0.36–0.94). To initiate taking folic acid supplementation early before conception was adversely associated with preterm birth risk (OR 0.89, 95% CI 0.83–0.95). In conclusion, higher maternal folate levels and folic acid supplementation were significantly associated with a lower risk of preterm birth. The limited data currently available suggest that dietary folate is associated with a significantly decreased risk of preterm birth.